Over a decade of HIV infection prevalence and incidence among Mozambican pregnant women: a secondary analysis of prospectively collected data - Anete Mendes-Muxlhanga; Arsénio Nhacolo; Antia Figueroa-Romero; Maura Mazuze; Alfredo Mayor; Anifa Vala; Esperança Sevene; Aleny Couto; Namita Eliseu; Llorenç Quintó; Gloria Matabisso; Eusebio Macete; et al. (BMC Public Health)
Abstract Background Monitoring HIV infection estimates is critical to guide health interventions and assess their impact, especially in highly vulnerable groups to the infection such as African pregnant women. This study describes the trends of HIV infection over eleven years in women attending selected antenatal care (ANC) clinics from southern Mozambique. Methods We performed a secondary analysis of data registered at the ANC clinic of the Manhiça District Hospital and from the Ministry of Health's HIV National Program Registry between 2010 and 2021. HIV incidence was calculated using prevalence estimates. HIV incidence trends over time were obtained by fitting splines regression model. Results Data from 21,810 pregnant women were included in the analysis. Overall HIV prevalence was 29.3% (95% CI: 28.7–29.9), with a reduction from 28.2% (95% CI: 25.6–30.8) in 2010 to 21.7% (95% CI: 19.8–23.6) in 2021, except for a peak in prevalence (35.3%, 95% CI: 30.1–40.8) in 2016. Over the study period, by maternal age group, the largest reduction in HIV prevalence was in the 15–20 year-old group [62% reduction, from 14.3% (95% CI 10.8–18.4) to 5.3% (95% CI: 3.6–7.5)], followed by the 20–25 year old group [43% reduction, from 29.0% (95% CI: 24.2–34.5) to 16.6% (95% CI: 13.6–19.8)] and the 25–30 year old group [13% reduction, from 36.9% (95% CI: 31.0–43.1) to 32.0% (95% CI: 27.3–37.0)] (p < 0.001). Incidence of HIV infection increased from 12.75 per 100 person-years in 2010 to 18.65 per 100 person-years in 2018, and then decreased to 11.48 per 100 person-years in 2021. Conclusions The prevalence of HIV decreased while the overall incidence stayed similar in Mozambican pregnant women, during 2010 to 2021. However, both estimates remain unacceptably high, which indicates the need to revise current preventive policies and implement effective ones to improve HIV control among pregnant women.